Computer Forums 1 = 2

11-15-2005, 06:09 PM   #11
Golden Master

Join Date: Mar 2005
Posts: 13,091
Re: 1 = 2

I dunno...Yeah, i did domething wrong... how could B/2= 1? b/2 = 0.5B OR 1/2B

Quote:
 Originally Posted by draconum Plus I dought A^2 = AB is hardly proven. Chris
A^2 is AxA

If B=A then,

A^2=AB, since B=A and A^2 is AxA
__________________

__________________

 11-15-2005, 06:14 PM #12 Fully Optimized     Join Date: Oct 2005 Posts: 2,958 Re: 1 = 2 lol, i did this problem before __________________ __________________
11-15-2005, 06:27 PM   #13
In Runtime

Join Date: May 2004
Posts: 399
Re: 1 = 2

Quote:
 Originally Posted by spank_fusion (A + B)(A - B) = B(A - B) A + B = B B + B = B 2B = B 2 = 1 And there you have it! One is equal to two. Your goal? Find the error in the proof. First to find it gets a big bear hug from a mushroom.
Ok, you can't divide both sides by (A-B) because you have to multiply out the brackets first. Didn't I already say this?

Yes, as in real-life, rules need to be followed in maths. Which makes me wonder whether there is any validity to it at all. Why can't it all just fall into place instead of someone having to make up "rules"? Seems strange that you have to follow things in a certain order, decided by some person (or group), to come to the universally agreed solution, doesn't it?

Weird I think you better put us out of our misery... please. My head hurts.
__________________

 11-15-2005, 06:33 PM #14 In Runtime     Join Date: Nov 2005 Posts: 366 Re: 1 = 2 I feel very ill! __________________ White Bear Lake, Minnesota GoldWings Rule!
11-15-2005, 08:16 PM   #15
Golden Master

Join Date: Mar 2005
Posts: 13,091
Re: 1 = 2

Quote:
 Originally Posted by Teencompwiz2 lol, i did this problem before
Then do it!
__________________

11-15-2005, 08:38 PM   #16
BSOD

Join Date: May 2005
Posts: 2,734
Re: 1 = 2

Quote:
 Originally Posted by CJ Ok, you can't divide both sides by (A-B) because you have to multiply out the brackets first. Didn't I already say this? Yes, as in real-life, rules need to be followed in maths. Which makes me wonder whether there is any validity to it at all. Why can't it all just fall into place instead of someone having to make up "rules"? Seems strange that you have to follow things in a certain order, decided by some person (or group), to come to the universally agreed solution, doesn't it? Weird I think you better put us out of our misery... please. My head hurts.
Haha, I'm not making up any rules! It's a simple algebraic proof. All the steps are valid. And I'll tell you all the problem soon enough, but it's only been a day! Come on guys - THINK!
__________________

 11-15-2005, 08:55 PM #17 In Runtime     Join Date: May 2004 Posts: 399 Re: 1 = 2 I was meaning algebra (and maths) in general, not you matey. (A + B)(A - B) = B(A - B) A + B = B This part doesn't make sense because you either can't divide both sides by (A-B) or you have opened up the brackets on the left. It should be: 0 = B(A-B) 0 = BA - B^2 BA = B^2 A = B __________________
 11-15-2005, 09:11 PM #18 Daemon Poster     Join Date: Mar 2005 Posts: 1,365 Re: 1 = 2 lol, we're all math heads here :P Yeah it's a pretty simple quesiton I was just getting ahead of myself for a second. But I love math anyways so I don't care. Chris __________________ My Computer: Mother Board: MSI K8N Neo4 Platinum/SLI --- CPU: AMD Athlon 64 3200+ PSU: OCZ ModStream 520w ----------------- HD: Seagate Barracuda 200g Video Card: XFX GeForce 6200 -------------- RAM: OCZ Value ram Dual Channel 256 x2
11-15-2005, 10:04 PM   #19
BSOD

Join Date: May 2005
Posts: 2,734
Re: 1 = 2

Quote:
 Originally Posted by CJ I was meaning algebra (and maths) in general, not you matey. (A + B)(A - B) = B(A - B) A + B = B This part doesn't make sense because you either can't divide both sides by (A-B) or you have opened up the brackets on the left. It should be: 0 = B(A-B) 0 = BA - B^2 BA = B^2 A = B

But yeah, it's legal to divide out the (A - B) since it's a whole term.
__________________

 11-15-2005, 11:01 PM #20 Baseband Member     Join Date: Dec 2004 Posts: 59 Re: 1 = 2 AČ = AB AČ - BČ = AB - BČ (A + B)(A - B) = B(A - B) A + B = B B + B = B 2B = B 2 = 1 The fun part comes in at step 2, when you set the entire equation to 0. Game over after it equals zero. =) __________________ __________________